دراسة تحليلية لمؤشر ممارسة الاعمال في الجزائر خلال الفترة 2016-2020 - بعضي, آسيا (جامعة الوادي - University of eloued, 2022)
تهدف هذه الورقة الى دراسة مدى سهولة ممارسة الاعمال في الجزائر، من خلال دراسة تحليلية لتطور مؤشر سهولة ممارسة الاعمال في الجزائر والمؤشرات الفرعية في الفترة الممتدة من 2016-2020 .بالاعتماد على التقارير الصادرة من مجموعة البنك الدولي . توصلت الدراسة الى ان الجزائر بقيت في المراكز المتخلفة في مؤشر ممارسة الأعمال، وذلك لتخلفها في اغلب المؤشرات الفرعية للمؤشر، وعدم كفاية الاصلاحات التي قامت بها الجزائر في تحسين وضعية ممارسة الاعمال Abstract: This paper aims to study the ease of doing business in Algeria, through an analytical study of the evolution of the ease of doing business index in Algeria and its sub-indicators in the period from 2016-2020, based on reports issued by the World Bank Group. The study concluded that Algeria remained in the backward positions in the Doing Business Index, due to its backwardness in most of the sub-indicators specified for the index, and the insufficiency of the reforms undertaken by Algeria in improving the status of doing business.
An analytical study of the ease of doing business indicator in Algeria during period 2016-2020
مقال
Keywords: لة ; مؤشر سهولة ممارسة الاعمال ; الجزائر